Trends in residential sustainability measures in the state of Victoria. Issue 2 (1st November 2022) - Crawford, R H; Paton-Cole, V; Turnbull, R; Fitzgerald, E; Michalewicz, A; Garber, J
Abstract: Buildings require a significant quantity of energy and water during their operation. Solar water heaters and rainwater tanks have become increasingly common to reduce the demand for fossil-fuel based energy and mains water within buildings. Since 2006, the Victorian Building Authority has required either a rainwater tank or solar water heater to be installed in any new house built in Victoria, Australia. This research analyses the trend in adoption of these two systems using data from building permits issued from 2006 to 2019. This shows that despite an initial preference for rainwater tanks, solar water heaters have been the preferred choice. This preference was found to be greatest for projects costing from $200k-$600k and for allotment areas smaller than 500 m 2 . Preference for rainwater tanks tended to increase in line with an increase in project cost and allotment area, and this preference was found to be most common in metropolitan areas. This study provides insight into the opportunities for further adoption of solar water heaters and rainwater tanks, including using information at the LGA level to develop specific business opportunities or to inform policy, such as alternative water efficiency solutions for households where allotment area may limit rainwater tank adoption.